Combined hydrothermal and free nitrous acid, alkali and acid pretreatment for biomethane recovery from municipal sludge. (15th July 2021) - Kakar, Farokh laqa; Purohit, Neha; Okoye, Frances; Liss, Steven N.; Elbeshbishy, Elsayed
Highlights: Individual and combined chemical and HTP pretreatments have been investigated. COD solubilization for combined pretreatment was not notably higher than the HTP. The highest methane yield was achieved for combined HTP with FNA. Reaction Curve and First-Order models were applied and found to fit the experimental data. Preliminary economic analysis indicated that combined HTP with FNA is feasible. Abstract: This study focused on investigating the effect of combined chemical and hydrothermal pretreatment (HTP) on the anaerobic digestibility of thickened waste activated sludge (TWAS). Three different combined pretreatment conditions of HTP + free nitrous acid (FNA), HTP + Acid, and HTP + Alkaline were applied to TWAS. To control and compare the effect of combined pretreatments and a single pretreatment, Acid, Alkaline, FNA and HTP pretreatments were applied done prior to AD. The results of this study revealed that combined pretreatments have higher potential to improve methane production yield and rate but not in the solubilization of COD. The highest methane yield of 275 mL CH4 /g TCOD added was achieved for the combined pretreatment with FNA and HTP. HTP + FNA pretreatment was found to produce higher methane yields compared to the combination of other typical acid and alkaline reagents with hydrothermal pretreatment. Methane yields of 594, 527, and 544 L CH4 /g VSS added, were achieved for HTP + FNA, HTP + ALK, and HTP + ACID pretreatments, respectively. The preliminary economic analysis showed that out of the combined pretreatment, only combining HTP with FNA is economically feasible.